Environmental management needs the support of secure rights and appropriate governance - Barrow, Edmund (International Food Policy Research Institute, 2021)
By 2050, 95 percent of Earth’s land will be degraded. Already, 24 billion tons of soil have been eroded by unsustainable agriculture (Larbodière et al. 2020). In 2020 alone, over 4 million hectares of primary forest were cleared, up 12 percent from 2019. Global trade, consumption, population growth, and urbanization are driving transformations that, in part, drive the destruction of nature. The 2020 Global Living Planet Index shows a 68 percent drop in populations of monitored species from 1970 to 2016. Such trends are a measure of declining ecosystem health (WWF 2020), and the World Economic Forum ranks biodiversity loss as a top-five risk to the global economy. Clearly, our environment must be high on political and agendas — yet too often environmental governance is weak and implementation is neglected.